Peningkatan Hasil Belajar Siswa Dengan Model Pembelajaran Cooperative Script Berbantuan Media Kartu Berpasangan di SMP Negeri Satap Matawai Iwi: (Improving Student Learning Outcomes with Cooperative Script Learning Model Assisted by Paired Card Media at SMP Negeri Satap Matawai Iwi) - Tamu ina, Ance; Tamu ina, Anita; Ndjoeroemana, Yohana (BIODIK, 2025)
This research was conducted to improve learning outcomes using the Cooperative Script learning model with the help of paired card media. This type of research is Classroom Action Research (PTK) consisting of pre-cycle, Cycle I, and Cycle II. Each cycle consists of four stages, namely, planning, implementation, observation, and reflection. In the pre-cycle the average score was 57.9%, 10 people completed it with a percentage of 41.66% and 14 students did not complete it with a percentage of 58.33%. In the activity, namely the affective aspect, there were 4 students with a good rating, 10 students with a fairly good rating, and 10 students with a poor rating. The average score for student cognitive in cycle I was 72.0%, of which 15 students completed with a percentage of 62.5% and 9 students did not complete with a percentage of 37.5%. Student activities, namely the affective aspect, there are 5 students with a very good predicate, 15 students with a good predicate, and 4 students with quite good predicate. Cognitive cycle II students with an average of 85% in cycle II completed 22 students with a percentage of 91.66% and 2 students who did not complete with a percentage of 8.33%.  Student activity is the affective aspect, there are 21 students with a very good predicate, and 3 students with a good predicate. It was concluded that the application of the Cooperative Script learning model assisted by paired card media could improve student learning outcomes in class VIII human respiratory system material at Satap Matawai Iwi State Middle School. Abstrak. Penelitian ini dilakukan untuk meningkatkan hasil belajar menggunakan model pembelajaran Cooperative Script dengan berbantuan media kartu berpasangan. Jenis penelitian ini yaitu Penelitian Tindakan Kelas (PTK) terdiri dari prasiklus, Siklus I, Siklus II. Tiap Siklus terdiri empat tahapan yaitu, perencanaan, pelaksanaan, observasi, dan refleksi. Pada prasiklus nilai rata-rata 57,9% yang tuntas 10 orang dengan presentase 41,66% dan siswa yang tidak tuntas 14 orang dengan presentase 58,33%. Aktivitas yaitu aspek afektif terdapat terdapat 4 orang siswa yang predikat baik, 10 orang siswa dengan predikat cukup baik, dan 10 orang siswa dengan predikat kurang baik. Kognitif siswa pada siklus I nilai rata-rata seluruh siswa 72.0% yang tuntas  15 orang siswa dengan presentase 62,5% dan siswa yang tidak tuntas 9 orang siswa dengan presentase 37,5%. Aktivitas siswa yaitu aspek afektif terdapat 5 orang siswa dengan predikat sangat baik, 15 orang siswa yang predikat baik, 4 orang siswa dengan predikat cukup baik. Kognitif siswa siklus II dengan rata-rata siklus II 85% yang tuntas 22 orang siswa dengan presentase 91,66% dan siswa yang tidak tuntas 2 orang siswa dengan presentase 8,33%.  Aktivitas siswa yaitu aspek afektif yang terdapat 21 orang siswa dengan predikat sangat baik, 3 orang siswa dengan predikat baik. Disimpulkan bahwa penerapan model pembelajaran Cooperative Script  berbantuan media kartu berpasangan dapat meningkatkan hasil belajar siswa Pada materi sistem pernapasan pada manusia kelas VIII di SMP Negeri Satap Matawai Iwi.